(untitled) (Bangladesh Journal of Medical Microbiology, 2012)
Calprotectin is a calcium and zinc binding protein released from leucocytes, markedly elevated in organic bowel diseases (OBD). Faecal calprotectin (FC) is supposed to be a reliable biomarker to screen the suspected patients with OBD. This study was aimed to determine the role of FC level in screening the suspected OBD patients. It was carried out by measurement of FC using a commercially available ELISA kit among 50 patients with chronic diarrhoea for ? 6 weeks with or without other GIT symptoms who underwent colonoscopic evaluation (35 OBD patients and 15 disease control) and 12 healthy control. Significantly higher value (P<0.001) of FC level were observed among OBD patients (n=35) (479.5+133µg/g) than those in disease control (n=15) (82.17+75.64µg/g) and healthy control (n=12) (27+18.2µg/g). Measurement of FC in diagnosing OBD revealed the sensitivity 100%, specificity 67%, PPV 88% and NPV 100%. FC can be used as a reliable biomarker in screening of suspected OBD by selecting the patients who need colonoscopy. DOI: http://dx.doi.org/10.3329/bjmm.v6i1.19353 Bangladesh J Med Microbiol 2012; 06(01): 7-10